Qualidade de vida em mulheres no climatério atendidas na atenção básica de Promissão-SP - Miranda, Jéssica Steffany [UNESP] (2013)
The comprehensive care to women's health requires assistance in all phases of his life. The climacteric, it comprises a relatively long period of woman's life, deserves increased attention from society because life expectancy after menopause is currently equivalent to the period of reproductive life. This study aimed to evaluate the quality of life of women in the municipality of Promissão/SP who are going through this phase with or without use of hormone replacement therapy (HRT). This was a longitudinal epidemiological study with a sample of 99 women in each group. We evaluated the sociodemographic, clinical and behavioral. Applied Menopause Rating Scale (MRS) to assess the intensity of climacteric symptoms and the Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) to assess quality of life. In the data analysis used the Student t test, chi-square and Tukey. HRT users had a mean age of 50.76 ± 3.63 years and nonusers of 48.95 ± 6.27 years (p = 0.01). There was no statistically significant difference in marital status (p = <0.001). Users reported a higher frequency of climacteric symptoms of mild to moderate intensity. Of the eight domains of quality of life assessed only social scored below 50 for the two groups. It stands out with the pain domain scores around 60. Vasomotor phenomena also with scores above 50 were shown to MRS. There were differences between the groups in relation to the components of the SF-36 and MRS to general health, functional capacity, lower capacity, depression, insomnia and vasomotor phenomena. Women users and nonusers of HRT had good quality of life